Sounds of Resistance: A Socio-Political Critique of Post-war Croatia Through the Lenses of Music - Marković, Ana (Music with a Message: Words, Music and Propaganda 2, 2025)
This chapter analyses the emergence and development of socially engaged music in Croatia during the post-war transition period from the end of the Homeland war until the present. A content analysis of fifty socially engaged songs by Croatian musicians will identify main themes concerning how socially engaged music reflected the social, political, and economic realities of this period. Following the content analysis, three major themes emerge: a critique of the corrupt and criminal system, a critique of society, and a critique of the Balkans in general. The findings suggest that socially engaged music in Croatia continues to be a valuable tool for addressing social and political issues in the country. The themes that emerge from the analysis highlight the ways in which socially engaged musicians in Croatia are using their music to call attention to important social issues and inspire change.